Ferromagnetism in undoped ZnO nanostructures synthesized by solution plasma process - Kim, Soo-Whan; Lee, Sunghun; Saqib, Ahmad Nauman Shah; Lee, Young Haeng; Jung, Myung-Hwa (ELSEVIER SCIENCE BV, 2017)
Ferromagnetism in undoped metal oxide nanostructures provides a precious platform for realizing advanced nanoelectronic and spintronic applications. Such ferromagnetism is dependent on various factors. In this work, we report the ferromagnetism of undoped ZnO nanostructures for different discharge times from 10 to 40 min by employing solution plasma process, which has a great benefit for the synthesis of nanostructures due to relatively facile and cost-effective method. Through crystallographic and morphological characterization, we reveal how crystallite size and morphological change affect the magnetic properties of ZnO nanostructures. Moreover, ZnO nanostructures discharged for 30 min show the strongest ferromagnetic behavior, which could be explained by the combined effect of more oxygen vacancies and larger surface to volume ratio. Our work paves the way for attempts to develop the ferromagnetism of metal oxide nanostructures for applications in nanoelectronics and spintronics. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: ROOM-TEMPERATURE FERROMAGNETISM; ZINC-OXIDE; DEPENDENCE; NANOPARTICLES; FILMS